Bio-Protection as an Alternative to Sulphites: Impact on Chemical and Microbial Characteristics of Red Wines - Simonin, Scott; Roullier-Gall, Chloé; Ballester, Jordi; Schmitt-Kopplin, Philippe; Quintanilla-Casas, Beatriz; Vichi, Stefania; Peyron, Dominique; Alexandre, Hervé; Tourdot-Maréchal, Raphaëlle (Frontiers in Microbiology, 2020)
In wine, one method of limiting the addition of sulphites, a harmful and allergenic agent, is bio-protection. This practice consists of the early addition of microorganisms on grape must before fermentation. Non-Saccharomyces yeasts have been proposed as an interesting alternative to sulphite addition. However, scientific data proving the effectiveness of bio-protection remains sparse. This study provides the first analysis of the chemical and microbiological effects of a Metschnikowia pulcherrima strain inoculated at the beginning of the red winemaking process in three wineries as an alternative to sulphiting. Like sulphiting, bio-protection effectively limited the growth of spoilage microbiota and had no influence on the phenolic compounds protecting musts and wine from oxidation. The bio-protection had no effect on the volatile compounds and the sensory differences were dependent on the experimental sites. However, a non-targeted metabolomic analysis by FTICR-MS highlighted a bio-protection signature.